Medical Emergency Management in Dental Practice: Proactive Risk Stratification and Simulation-Driven Clinical Readiness - Dwi Riski Saputra; Hendrijaya Permana; Zainul Cholid (Jurnal Kegawatdaruratan Medis Indonesia, 2026)
The increasing prevalence of geriatric patients with complex comorbidities and polypharmacy has significantly elevated the incidence of chairside medical emergencies in dental practice. Although oral and maxillofacial surgeons possess comprehensive theoretical knowledge of the pathophysiology underlying emergencies such as vasovagal syncope and hypoglycemia, a critical "action gap" persists between academic understanding and real-time crisis management. This review aims to present a clinically actionable framework encompassing early detection, precision prevention protocols, and advanced stabilization strategies to optimize patient safety. A comprehensive literature search was conducted across PubMed, Scopus, and Google Scholar databases through early 2026, focusing on pre-procedural risk stratification, intraoperative Basic Life Support (BLS) competencies, and the measurable impact of high-fidelity simulation training. Findings demonstrate that formalized risk-matrix screening effectively prevents systemic crises through proactive treatment modifications. Importantly, evidence indicates that conventional didactic education is insufficient; only regular, simulation-based emergency drills successfully bridge this gap by enhancing stress-resilient psychomotor skills and team-based cardiopulmonary resuscitation performance. In conclusion, effective management of maxillofacial emergencies depends on proactive risk profiling and institutionalizing a culture of continuous simulation training. The transition from static theoretical knowledge to dynamic, simulation-driven clinical readiness represents the forefront of modern patient safety in dental practice prior to emergency medical services arrival.